Art Experience (AX): Scientific, Technological and Economic Fields of Experience of Contemporary Art - Lang, Krzysztof (Edukacja Ekonomistów i Menedżerów, 2018)
The paper reviews and attempts to define artistic practices implemented in the areas of science, technology and business – perceived as research tools and used as a medium in communicating the results of scientific research. In order to achieve the assumed goal, the examples of selected artistic practices conducted by scientists and curators working for scientific, research and cultural heritage institutions as well as artists operating on the verge of art and science have been presented. The aspect related to the impact of contemporary arts in the public space has also been discussed. The preliminary analysis of these examples helped formulate the thesis about the growing role of artistic practices as research tools and the medium of communication in many fields of science, institutional and non‑institutional practices not directly related to the area of art.